ISSUES OF ATTRACTING GREEN TECHNOLOGIES IN THE DEVELOPMENT OF THE GREEN ECONOMY IN UZBEKISTAN (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This work covers the current issues of green economy and development of green technologies in Uzbekistan. In particular, the ongoing work and existing problems to ensure environmental sustainability, rational use of resources, introduction of renewable energy sources, emission reduction are analyzed. Technological innovations aimed at improving energy efficiency in the fields of electric power, thermal power and oil and gas industry are also mentioned. The work also took into account international experience and obligations under the Paris Agreement.